Predicting barbell release speed from peak speed in the bench press throw via a linear position transducer - Henneberry, M. C.; Agar-Newman, D.; Lenetsky, S.; Klimstra, M. D. (Measurement in Physical Education and Exercise Science, 2024)
Upper body force-velocity profiles to assess musculoskeletal performance are created using release speed (RS) of the barbell in a bench press throw (BPT). A more easily obtained variable is peak speed (PS) measured by a linear position transducer. We assessed the validity of predicting RS from measured PS. One hundred and seventy-eight throws from ten male participants age (mean ± SD) 27 ± 5 yrs, mass 88 ± 13 kg with minimum one year of resistance training performed the BPT with increasing loads on a Smith machine. Correlation revealed an exponential relationship of RS = 0.26e0.9(PS), (R2 = 0.96, p < .05). We assessed predictive validity by comparing the measured RS of the barbell in each throw to the RS estimated by this formula. Bland-Altman analysis showed the 95% limit of agreement was 0.26 m·s-1 to 0.18 m·s-1, with a mean difference of 0.04 m·s-1 (2.92%), determining that PS may be used to estimate RS.